A Fault-Diagnosis Algorithm-Embedded Controller Design for Hydraulic Solenoid Valves in Industrial Applications - Yoo, Seungjin; Jung, Joon Ha; Lee, Jai Kyung; Shin, Sang Woo; Jang, Dal Sik (International Journal of Precision Engineering and Manufacturing, 2025)
Hydraulic solenoid valves (HSVs) are widely used for fluid control in industrial applications. Like other mechanical parts, HSVs deteriorate and faults occur during their use in industrial settings. Although several prior fault-diagnosis methods have been proposed to detect these faults, previous studies have not considered the actual implementation of the methods on the controller. Thus, to ensure reliable operation of HSVs in the field, this research paper presents an innovative HSV controller design that is able to process the proposed fault-diagnosis algorithm. In the proposed work, the hardware is designed to transmit and receive signals and data for the valve-diagnosis algorithm. For the software, an architecture is proposed to enable the fault-diagnosis algorithm to be processed in a conventional microprocessor. In this research, the proposed controller design was built and tested on an actual hydraulic system. The results show that the proposed fault-diagnosis algorithm has been successfully embedded in the microcontroller.
Keywords: Controller designs; Diagnosis algorithms; Embedded controllers; Faults diagnosis; Fluid control; Hardware design; Hydraulic solenoid valve; Mechanical parts; Software and hardware design; Software and hardwares; Controller; Fault diagnosis; Hydraulic solenoid valve; Microprocessor; Software and hardware design